AB0397 Prevalence and factors associated with depression among patients affected by chronic inflammatory arthritis: preliminary results of a single-centre experience in italy. (12th June 2018) - Pezzato, S.; Tomassi, S.; Fracassi, E.; Giollo, A.; Caimmi, C.; Martinis, F.; Gnatta, M.G.; Cristofalo, D.; Bonetto, C.; Marognolli, M.L.; Tosato, S.; Carletto, A.
Abstract : Background: Depression and anxiety disorders are more common in chronic inflammatory arthritides (CIA) than in the general population. 1 In rheumatoid arthritis (RA), depressive and anxiety symptoms have been associated with disease activity and pain perception, 1 physical disability, 2 health care costs, 3 and mortality. 4 To our knowledge, data on the prevalence of depression in Italian patients with RA are scarce. Objectives: To estimate the prevalence and factors associated with depression among patients affected by RA. Methods: During an one year period, patients affected by RA have been consecutively enrolled. For each patient demographics and disease characteristics were recorded; the Hospital Anxiety and Depression Scale (HADS) was administered. HADS is a validate questionnaire to assess depressive and anxiety symptoms in patients affected by somatic disorders admitted to general hospital. An HADS ≥11 was considered diagnostic for depression. Results: The table summarises the main results. We recruited 231 patients affected by RA, finding a prevalence of depression of 13.9% (95% CI 9.4%–18.3%). Overall, patients with depression, when compared with patients without, were older, more frequently females, with a lower education, higher physician global assessment and patient global assessment, more comorbidities. In particular, they had any cardiovascular, neurologic or musculoskeletal issue (p=0.018, p=0.032, p=0.014, respectively) and more often used glucocorticoids or NSAIDs. Conversely, no association was found between depressive symptoms and the use of biologic therapies or the presence of inflammatory markers. Interestingly, a positive history of depression was present only in few patients with an HADS ≥11. Conclusions: These preliminary results suggest that more than one every seven patients with RA could suffer from depression, thus depression might be undiagnosed in a significant number of patients. Comorbidities, anti-inflammatory medications and both physician- and patient- driven evaluation of disease burden were the most striking factors associated with depression in this cohort of patients with RA. References: [1] Kojima M, et al. Arthritis and rheumatism2009Aug 15;61(8):1018–24. [2] Peck JR, et al. Arthritis and rheumatism1989Sep;32(9):1100–6. [3] Joyce AT, et al. J Rheumatol2009Apr;36(4):743–52. [4] Ang DC, et al. J Rheumatol2005Jun;32(6):1013–9. Disclosure of Interest: None declared